If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3x = 2 + 6x Solving 5 + 3x = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + 3x + -6x = 2 + 6x + -6x Combine like terms: 3x + -6x = -3x 5 + -3x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 5 + -3x = 2 + 0 5 + -3x = 2 Add '-5' to each side of the equation. 5 + -5 + -3x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 2 + -5 -3x = 2 + -5 Combine like terms: 2 + -5 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 3/4x+26=18 | | 4x-5x^2/x | | 2x-3(1)=-7 | | 26-3/4x=18 | | 5-3x=84+6x | | 12+14=3*f | | 5-3x=4+6x | | 6-8(5-3x)=0 | | 52+g=45+11 | | 2-6x=4+8x | | 4(6x-7)=32x | | 2-6x=14+8x | | z-51/6=116/7 | | 37+s=80/2 | | 3y-12x=18 | | H=16t^2-180t | | 2-3x=4+10x | | (3+2-2-1)(4+-1+-3)= | | 2-3x=4+8x | | 420/d=30 | | 2-3x=14+8x | | 5-3x=14+4x | | (5e^2j)/(4+5j) | | 5-3x=14+8x | | 57+4m=0 | | 5-3x=10+8x | | 5-6x=10+8x | | 5-6x=10+6x | | 2(-9.5)-3(1)= | | 100[0.07(x+7)]= | | 9(x+5)-9=40-3x-4+12x | | 0.4(0.1x+0.5)=-0.4 |